The Influence of Work Discipline and Motivation on Job Satisfaction in Public Transportation Companies in Bandung City - Apina Auliya; Andhika Mochamad Siddiq; Ridlwan Muttaqin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study's backdrop is a decrease in staff attendance and a rise in tardiness., which indicate the existence of job satisfaction problems. Job satisfaction refers to the supportive or unsupportive feelings experienced by employees in carrying out their work, both in relation to their tasks and their personal conditions (Mangkunegara, 2017). The purpose of this research is to examine and examine the effect of work discipline and motivation on job satisfaction at a public transportation company in Bandung City. The population of this study consists of 70 employees. A quantitative technique is used as the research methodology, using information gathered by distributing surveys to all employees as research respondents. The study's results indicate that all variables are classified at a low level It seems from the results of the partial test that work discipline has a favorable influence on job satisfaction, although this effect is not statistically significant. Meanwhile, motivation has a positive and significant effect on job satisfaction. Simultaneously, work discipline and motivation have a positive and significant effect on employee job satisfaction. In light of these findings, one may deduce that the levels of job satisfaction, work discipline, and employee motivation at the public transportation company in Bandung City are in the low category. Therefore, efforts to enhance employee job satisfaction should focus on strengthening work motivation, accompanied by continuous improvements in work discipline.